Phonological awareness and early reading skills in children with cochlear implants. (May 2014) - Ching, Teresa YC; Day, Julia; Cupples, Linda
<x content-type="archive" xml:space="preserve">Abstract</x> This paper summarizes findings from a population study on outcomes of children with hearing loss in Australia, the Longitudinal Outcomes of Children with Hearing Impairment (http://www.outcomes.nal.gov.au) study. Children were evaluated at several intervals using standardized tests, and the relationship between a range of predictors and the outcomes was examined. This paper reports the performance of children with cochlear implants at 5 years of age together with factors predicting word reading ability. Earlier age at cochlear implantation was significantly associated with better word reading ability, after controlling for the effects of language, receptive vocabulary, nonverbal cognitive ability, and device configuration.